MENGATASI MASALAH HETEROSKEDASTISITAS DENGAN MENGASUMSIKAN VARIANS VARIABEL GANGGUANNYA PROPORSIONAL DENGAN X_i^2 DAN [E(Y_i)]^2 - GUNAWAN, MADE ADI; HARINI, LUH PUTU IDA; ASIH, MADE (E-Jurnal Matematika, 2014)
The volatilities of time series data often experience heteroscedastic problems. Heteroscedasticity is a nuisance variable in the regression equation having a variance that is not constant. Therefore, methods to analyze the problem of heteroscedasticity are needed. This study aims to demonstrate how to eliminate the problem of heteroscedasticity. The method used is, GoldFeld-Quandt. As for eliminating the problem of heteroscedasticity by assuming the variance of interference variables proportional to E(Yi)2
Keywords: Arbitrage Pricing Theory; Granger causality test; optimal lag test; Portmanteau test; stationary test; Vector Autoregression